Evaluation of morphological features and performances of Aseel chicken of Bangladesh under intensive management condition (Bangladesh Journal of Animal Science, 2026)
The current study was aimed to evaluate morphometric features along with productive and reproductive performances of indigenous Aseel chicken of Bangladesh under intensive management condition. The experiment was conducted from day old to 40th week of age including a total of 54 Aseel chicken (25 male and 29 female). The results show that yellow shank and beak, small wattles in male, small-red earlobe, white skin, yellow eye and light brown eggs were dominant characters in Aseel chicken. Radius length, keel length, shank length and drumstick length were 8.44±0.09, 10.63±0.15, 9.59±0.11 and 7.59±0.05 cm, respectively, in females and corresponding values were 9.88±0.14, 12.73±0.15, 12.11±0.21 and 10.67±0.16 cm in male. Moreover, the body weight at day old, 1st, 2nd, 4th, 6th, 8th, 12th, 16th, 20th and 40th weeks of age were 22.69±0.74, 32.71±1.74, 58.84±4.35, 215.47±8.86, 364.82±15.43, 576.00±16.33, 807.19±19.07, 1059.61±22.24, 1630.29±34.92, 2150.49±42.27 and 2956.25±46.86 g, respectively in this experiment. Feed conversion ratio (FCR) were 1.76, 3.30, 4.41 and 4.93 at 1st, 4th, 8th and 12th weeks of age. The reproductive traits age at first lay (day), number of eggs per clutch, egg weight, fertility (%) on total egg, hatchability (%) on fertile egg and mortality (%) up to 40th week of age were 142±0.83, 18.67±1.17, 35.84±0.68, 58.81, 88.29 and 3.70%, respectively. This study provides some important baseline information of Aseel chicken that could be utilized in genetic improvement and conservation of this valuable genetic resource of Bangladesh.Bangladesh Journal of Animal Science 55 (1): 13 - 20, 2026